Influence of advertisments on changes in the urban structure of cites on the example of Poznan = Wpływ reklam na zmiany struktury urbanistycznej miast na przykładzie Poznania - Bonenberg, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of studies on the influence of outdoor advertisements on the activation of selected areas in the spatial structure of the city of Poznań. The contents of advertisements were analyzed in terms of the places which advertisements placed on signs, billboards and advertising displays located in public spaces direct us to. The results of studies indicated that the majority of advertisements located in the city center of Poznań promote suburban locations, encouraging its inhabitants to make use of trade and services outside of the strict city center.
Keywords: reklama zewnętrzna; przestrzeń publiczna; aktywizacja urbanistyczna; outdoor advertising; public space; urban activation